Whey Protein (Ma’aljobon) as a Complementary Therapy for Treatment of Attention-deficit/ Hyperactivity Disorder (ADHD): A Randomized Open-label Controlled Clinical Trial: - Mostajeran, Zeinab; Mosavat, Seyed Hamdollah; Najafi, Mostafa; Hashempur, Mohammad Hashem; Emtiazy, Majid (Galen Medical Journal, 2020)
Background: Attention deficit hyperactivity disorder (ADHD) is a common, chronic, neurodevelopmental disorder that manifests in childhood with symptoms of hyperactivity, inattention, and impulsivity. Ma’aljobon (a kind of whey protein) that is derived from milk during cheese producing process is a popular dietary traditional product supposed to provide immune modulation and prevent neuropsychiatric disorder. We aimed to evaluate the efficacy of ma’aljobon in management of Attention-deficit/hyperactivity disorder (ADHD). Materials and Methods: In this open-label randomized, double arm, and controlled clinical trial, sixty four patients with ADHD who referred to out-patient child and adolescent clinic of Khorshid Hospital of Isfahan, Iran, were randomly assigned in the intervention group (ma’aljobon 25 g once daily plus standard conventional treatment (SCT)) or control group (SCT only) for a period of 8 weeks. Scores of the Strengths and Difficulties Questionnaire (SDQ) and Conners’ Continuous Performance Test (CPT) were set as the outcome measures. Results: Parent reported hyperactivity scale of SDQ showed a significant decrease in the intervention group compared to the control group (P=0.04). However, no significant between groups differences were observed in other scales of parent-reported SDQ. Also, according to the results of CPT, there was a significant improvement in the intervention group regarding attention and focus score (P=0.01). Conclusion: Ma’aljobon might be considered as a complementary remedy for improving hyperactivity, attention and focus of children with ADHD. However, further researches with larger sample size and longer duration should be done for achieving more reliable results. [GMJ.2020;9:e1690]